A roadmap for maximizing the use and effectiveness of recovery housing for individuals prescribed medications for opiate use disorders - Amy A. Mericle; Carmen L. Masson; Sarah E. Zemore; Meenakshi S. Subbaraman; Dustin Khebzou; Diane Schmidt; Kwinoja Kapiteni; Leonard A. Jason (Frontiers in Public Health)
IntroductionSafe and stable housing is increasingly recognized as critical to recovery from alcohol and drug use disorders, but research on the outcomes of residents in recovery from opioid use disorder (OUD), particularly those prescribed medications for opioid use disorder (MOUD), is limited.MethodsThis article presents results from an informal survey (N = 15) and discussion with experts in the recovery housing and OUD treatment fields serving as Advisory Board members on the Infrastructure for Studying Treatment and Addiction Recovery Residences (I-STARR) project regarding priorities for research and training on recovery housing for individuals prescribed MOUD. Drawing on the results, we provide a roadmap to establish an evidence base on recovery housing for those prescribed MOUD.ResultsThree of the highest-ranked research topics identified were: (1) Assessment of recovery housing outcomes of people prescribed MOUD and factors that may influence outcomes; (2) Examination of factors associated with MOUD adherence among recovery housing residents; and (3) Strategies to increase linkage between MOUD prescribers/treatment providers and recovery residence operators. Additional topics emerged during discussion, most prominently the examination of barriers to, and facilitators of, accessing recovery housing among people prescribed MOUD. The highest-rated training topic for researchers and recovery housing operators was challenges faced by recovery housing operators.ConclusionResearch is urgently needed to establish an evidence base on recovery housing for those prescribed MOUD, and both researchers and operators in the field would benefit from training to ensure that potential challenges to moving research forward on this topic are addressed.